Efeito de reservatório de aproveitameto de água da chuva sobre redes de drenagem pluvial - Hentges, Sara Ceron (2013)
The urban growth and the disordered occupation of cities have increased the frequency and severity of flooding in urban areas, which occur mainly due to the modification on rainwater natural infiltration, as a result of soil imperviousness increase. The use of compensatory techniques (CT) for stormwater control has been encouraged through public polices, attempting to apply for sustainable solutions to mitigate the urbanization´s impact. An alternative already widespread in some Brazilian cities is the use of micro reservoirs (MR), which temporarily store volumes from impervious areas, and gradually emptying the water stored. Along this requirement, implementation of Rainwater Harvesting Reservoirs (RHR) to non-potable purposes is often encouraged in order to reduce the consumption of drinking water for less noble purposes, and to preserve the fountainheads. Some bibliographies suggest that in addition to these benefits, the RHR can be considered a CT also, once it stores the stormwater runoff, and therefore, in some cities where the MR is required, many buildings are already using the RHR to replace it. However, there are not many conclusive studies related to the real benefits and impacts that capturing rainwater and its use have on micro drainage networks, and specifically if such technique can be considered as a compensatory one. Thus, the main objective of this research was to evaluate whether RHR can be considered as an alternative to promote the quantitative stormwater control. For that, a comparative analysis was made between the impact that RHR use generates on micro drainage flows and networks, and the impact generated on a MR containing system. Such analysis was performed through a modeling of a urban watershed from Porto Alegre / RS, with 977 ha, 30.720 standard lots and around 70 km of micro drainage networks. The simulated MRs were designed according to the Decree No. 15.371/06 of the city of Porto Alegre, which aim to control the runoff at the source and it resulted in volumes of 3.13 m³ and 3.75 m³ for rainfall project with return period of 5 and 10 years (CP-CP-TR5 and TR10), respectively, answering to the allowable flow restriction at the lot outlet (VR = 0.624 L / s). The micro drainage networks were designed for both situations, with and without MRs, for CP-TR5 and CP-TR10. For sizing of the RHRs a continuous simulation of 12 years of precipitation data and demands series for non-potable uses data was performed, both with time step equal 5 minutes, resulting in volumes of 5.000, 10.000 and 15.000 liters due to the achieved service guarantee. These volumes of RHRs replaced the MRs and new modeling were performed considering observed rainfall data real from the continuum time series. It was found that the RHRs were not effective to maintain the VR at lots outlet, and the restriction value was exceeded for several times. For the simulated time seriess only the volume of 750 m³ would be appropriate to ensure only one offense within 10 years of simulation. That occurs because must have sufficient volume to store the expected drained volume, without spillage, regardless of the reservoir storage condition. However, if there is a very large storage capacity and demands are comparatively small, the reservoir does not empty. It was found, therefore, that exists an antagonism when trying to use the RHR for two functions: runoff control and water supply for non-potable purposes demand, since the attempt to ensure the fulfillment to the first function prevents the deployment of such large volumes. Overtopping of RHRs to 12 critical simulated events committed the microdrainage networks capacity, generating flooding in the streets along several drainage network ranges. Considering the same 12 critical events and MRs in lots were identified only four overflowing and lower overflows, which ended up committing a lower extent of drainage networks. Therefore, based on analysis of the continuous simulation with RHRs, it was found that it is not possible to consider it an equivalent technique to the MRs for storm water runoff control, unless the reservation volumes are extremely high, which would make its implementation on a few square meters lot impossible.